Blood ketone measurement as a test for dietary compliance in cardiac sarcoid patients undergoing 18f-fluorodeoxyglucose positron emission tomography. (20th July 2021) - Clarke, S; Alves, F; Martins, N; Ahmed, M; Sanchez, L; Donovan, J; Kouranos, V; Wechalekar, K
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Imaging with 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) is used as part of diagnosis and monitoring response to therapy in patients with cardiac sarcoidosis. In order to supress myocardial uptake of 18F-FDG patients prepare with a low carbohydrate diet followed by an 18-hour overnight fast. Failure to comply with the protocol results in diffuse myocardial 18F-FDG uptake which confounds diagnostic interpretation. Purpose: To assess if point of care blood ketones could be used as a marker of dietary compliance and association with suppression of myocardial 18F-FDG uptake on PET scan. Method: Patients (n = 26, 57 ± 4 years, 65% Male) from a single centre were instructed to follow standard preparation protocol prior to 18F-FDG PET/CT. After confirmation of dietary compliance, blood glucose and blood ketones were recorded using point of care devices. Images were graded based on the pattern of myocardial 18F-FDG uptake. Results: There was no clear correlation between blood ketones in relation to dietary compliance or myocardial 18F-fluorodeoxyglucose uptake. In those with myocardial 18F-FDG uptake maximum standardized uptake value (SUV max) within the myocardium ranged from 2.3 to 9.8 (Mean 5.3) and ketone from 0.1 – 0.7 (normal <0.6). Non-diabetic patients and those on steroids achieved adequate fasting glucose without significant rise in blood ketones. 60% of diabetic patients demonstrated mildly elevated ketones between 0.6-1.5mmol/L. Conclusion: Current protocol with low carbohydrate diet and 18-hour fast achieves adequate quality of images in majority of patients, without significant change in blood ketones. Therefore, blood ketones cannot be used to confirm dietary compliance.  Diabetic patients on insulin may benefit from ketone measurement due to risk of diabetic ketoacidosis.